Comfort related woven fabric transmission properties made of cotton and nylon - Biruk Fentahun Adamu; Jing Gao (Fashion and Textiles, 2022)
Abstract The interaction of water and air i.e. moisture regain, water vapor transmission, wicking and air permeability with woven textiles are tested to investigate the comfort of woven fabrics made of nylon, cotton, and cotton–nylon mixtures with different yarn counts. The fabrics porosity (based on equation 1 and 2), woven fabric sett (ASTM D3775-03), fabric thickness (ASTM D1777-96), fabric weight (ASTM D3776M - 20), fabric vapour transmission (ASTM E96-00), transfer wicking, and longitudinal wicking (DIN 53924), moisture regain (ASTM D2495-07), and air permeability (ASTM D737) were examined for investigations based on the standards in the brackets. The experimental results showed that fabric transfer wicking, longitudinal wicking, moisture regain and air permeability properties increase as the yarn goes to coarser for all woven fabric samples but the water vapor transmission property decrease. Additionally, fabric transfer and longitudinal wicking capabilities improved with increased nylon fiber blend ratios within fiber conformation. However, the nylon fiber composition has negative impact on air permeability, water vapor transfer rate, wicking and moisture capabilities of the woven fabrics. Generally, it can be concluded that the existence of nylon fiber, and yarn count coarseness improved wicking properties of the woven fabrics and decreased the air permeability property of woven fabrics.